DOI: 10.1007/978-3-540-85099-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Recognition of Emotions from Speech: A Review of the Literature and Recommendations for Practical Realisation

Abstract: Abstract. In this article we give guidelines on how to address the major technical challenges of automatic emotion recognition from speech in human-computer interfaces, which include audio segmentation to find appropriate units for emotions, extraction of emotion relevant features, classification of emotions, and training databases with emotional speech. Research so far has mostly dealt with offline evaluation of vocal emotions, and online processing has hardly been addressed. Online processing is, however, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
3

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 35 publications
(40 reference statements)
1
64
0
3
Order By: Relevance
“…The intensity of sound (i.e., the pitch and volume) and the speed of articulation were considered to be the main indicators for distinguishing intensity, activation, and potency of clients' emotional states. This is consistent with studies of acoustics features in emotional expressions [46,47]. For example, there are influential associations between vocal cues (e.g., rate of speech, loudness) and emotions such as fear anxiety, sadness, and depression [48].…”
Section: Discussionsupporting
confidence: 87%
“…The intensity of sound (i.e., the pitch and volume) and the speed of articulation were considered to be the main indicators for distinguishing intensity, activation, and potency of clients' emotional states. This is consistent with studies of acoustics features in emotional expressions [46,47]. For example, there are influential associations between vocal cues (e.g., rate of speech, loudness) and emotions such as fear anxiety, sadness, and depression [48].…”
Section: Discussionsupporting
confidence: 87%
“…Great advances have been made during last decade on assessing human state through technical way. For example, speech emotion recognition works [1][2][3] have shown effectiveness of extracting emotional content from human speech signals. In addition, Deep Neural Networks (DNN) have been employed for many related speech tasks [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It may be also useful in automatic translation systems in which the emotional state of the speaker plays an important role in communication between parties. In aircraft cockpits, it has been found that speech recognition systems trained to stressedspeech achieve better performance than those trained by normal speech [6].…”
Section: Need Of Emotion Recognition Through Speechmentioning
confidence: 99%